Prediksi Harga Saham Perusahaan Perbankan Menggunakan Regresi Linear Studi Kasus Bank BCA Tahun 2015-2017 - Merfin Merfin; Raymond Sunardi Oetama (Ultimatics : Jurnal Teknik Informatika, 2019)
Stock investment is important for financial development in a company. Moreover, the stock price displayed by the company can be known by the people and the local economy because the company has gone public on the Indonesia Economic Exchange (IDX) at www.idx.co.id. There are several fundamental factors that influence the stock market price in a listed company and as a result the number of stock investors in Indonesia is very small. This cause made it difficult for the community to predict the stock price of banking companies at inconsistent prices. The method to be used in this paper is Linear Regression using Excel tools to perform calculations and SPSS 16.0 as a data mining tool. The research data taken is historical data of banking companies for 3 periods as a whole in the form of excel that has been downloaded from the Yahoo Finance website. The final results are in the form of MAPE charts in 3 years period, and Average error chart in 3 years period.